Work pressure and employment of housemaids among female bank (2012)
The employment of housemaids to reduce domestic and official work pressure is prevalent among career women in Nigeria, with implications for child socialization and domestic security. Employing the role strain theory, this study examined the coping strategies adopted by married female bankers as a way of understanding the context of work and family pressure. The data comprised 30 in-depth interviews and six Focus Group Discussions. The results indicate that the employment of housemaid was considered risky but necessary; respondents revealed that recruiting housemaid was a means of reducing pressure from role conflict arising from domestic and official work. The security and socialization of children were reported to be jeopardized as housemaids were inferior substitutes for maternal care and home-keeping. Also common among housemaids were desertion, stealing and sexual liaison with husbands. Among other recommendations, banks should device measures to enable married female staff to take adequate care of their children in close proximity to the workplace